CTRP3 attenuates diet-induced hepatic steatosis by regulating triglyceride metabolism - Peterson, Jonathan M. (American Physiological Society, 2013)
CTRP3 is a secreted plasma protein of the C1q family that helps regulate hepatic gluconeogenesis and is downregulated in a diet-induced obese state. However, the role of CTRP3 in regulating lipid metabolism has not been established. Here, we used a transgenic mouse model to address the potential function of CTRP3 in ameliorating high-fat diet-induced metabolic stress. Both transgenic and wild-type mice fed a high-fat diet showed similar body weight gain, food intake, and energy expenditure. Despite similar adiposity to wild-type mice upon diet-induced obesity (DIO), CTRP3 transgenic mice were strikingly resistant to the development of hepatic steatosis, had reduced serum TNF-α levels, and demonstrated a modest improvement in systemic insulin sensitivity. Additionally, reduced hepatic triglyceride levels were due to decreased expression of enzymes (GPAT, AGPAT, and DGAT) involved in triglyceride synthesis. Importantly, short-term daily administration of recombinant CTRP3 to DIO mice for 5 days was sufficient to improve the fatty liver phenotype, evident as reduced hepatic triglyceride content and expression of triglyceride synthesis genes. Consistent with a direct effect on liver cells, recombinant CTRP3 treatment reduced fatty acid synthesis and neutral lipid accumulation in cultured rat H4IIE hepatocytes. Together, these results establish a novel role for CTRP3 hormone in regulating hepatic lipid metabolism and highlight its protective function and therapeutic potential in attenuating hepatic steatosis.